2020
DOI: 10.7150/jca.44441
|View full text |Cite
|
Sign up to set email alerts
|

miR-223-5p targeting ERG inhibits prostate cancer cell proliferation and migration

Abstract: Ectopic expression of miR-223-5p, the lagging strand of miR-223 duplex, has been reported acting as anti-tumor miRNA in many cancers. How miR-223-5p influencing prostate cancer (PCa) remains obscure and worth of experimental investigation. In this study, the expressions of miR-223-5p and ERG in common PCa cell lines were detected and compared to RWPE-1, respectively. Then luciferase reporter assay was performed to verify whether miR-223-5p could specifically target and regulate ERG. Further discovery ERG's rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…miR-424 affects the ubiquitination and activation of STAT3 to promote prostate cancer development ( Dallavalle et al, 2016 ). In the present study, miR-233 was predicted to bind with circGNG4, and miR-223 has been determined to inhibit prostate cancer progression by targeting ETS transcription factor ERG (ERG) and integrin subunit α 3 (ITGA3)/integrin subunit β 1 (ITGB1) signaling ( Kurozumi et al, 2016 ; Wei et al, 2020 ). It is therefore hypothesized that circGNG4 exerts its oncogenic role via sponging miR-223, which blocks the anti-cancer effect of miR-233.…”
Section: Discussionmentioning
confidence: 94%
“…miR-424 affects the ubiquitination and activation of STAT3 to promote prostate cancer development ( Dallavalle et al, 2016 ). In the present study, miR-233 was predicted to bind with circGNG4, and miR-223 has been determined to inhibit prostate cancer progression by targeting ETS transcription factor ERG (ERG) and integrin subunit α 3 (ITGA3)/integrin subunit β 1 (ITGB1) signaling ( Kurozumi et al, 2016 ; Wei et al, 2020 ). It is therefore hypothesized that circGNG4 exerts its oncogenic role via sponging miR-223, which blocks the anti-cancer effect of miR-233.…”
Section: Discussionmentioning
confidence: 94%
“…Dou et al [ 45 ] confirmed that miR-223-5p suppressed tumor growth and metastasis in non-small-cell lung cancer by targeting E2F8 (encoding E2F transcription factor 8). Recent research also showed that miR-223-5p targets ERG (encoding ETS transcription factor ERG) and inhibited prostate cancer cell proliferation and migration [ 46 ]. In addition, miR-205-5p expression in breast cancer tissues and cell lines was decreased compared with that in normal tissues and a normal cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed that miR-223-5p is significantly downregulated in cancer tissues and cells, suggesting its inhibitory effect on tumor progression. For example, miR-223-5p may inhibit the progression of non-small cell lung cancer by modulating E2F transcription factor 8 (8), suppress the malignant phenotype of prostate cancer cells via modulating ETS transcription factor ERG (9) and repress the aggressiveness of bladder cancer cells (10). However, the potential regulatory role of miR-223-5p in NPC has not been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%